"Don't Just Randomly Grab Someone's Neck during Intercourse!" An Analysis of Internet Articles about Choking/Strangulation during Sex. Issue 1 (2nd January 2023) - Herbenick, Debby; Patterson, Callie; Khan, Shahzarin; Voorheis, Eva; Sullivan, Anne; Wright, Paul; Keene, Samantha
Abstract: Sexual choking/strangulation has become prevalent among young U.S. adults, yet little is known about media articles that teach readers about choking. We conducted a content analysis of 27 Internet articles, examining how choking is described, information related to health risks and healthcare, and article accuracy. Most articles described choking in positive terms and indicated choking can be done safely or properly, even while acknowledging potential dangers. Only two articles indicated having undergone expert/medical review. Few gave information about signs that would warrant seeking healthcare. Sexuality professionals need to be aware of choking-related information and misinformation in online media articles.